On the Introduction of Firing Costs - Steffen Ahrens; Dennis Wesselbaum (Verein für Socialpolitik, 2010)
This paper analysis two types of firing costs in a New Keynesian model with search and matching frictions and purely endogenous separations. We further distinguish between the effects resulting from respecting and non-respecting the bonding critique. We find that the two types of firing costs similarly influence the model dynamics and generate comparable second business cycle moments. However, the decision whether to respect or disrespect the bonding critique is crucial for the evolution of the system dynamics. This is especially true, when comparing American and European calibration.
Keywords: E24; E32; J64; 330; Beveridge Curve; Endogenous Separations; Firing Costs